Queue Optimization Study for Retail Efficiency Enhancement: Studi Optimalisasi Antrian untuk Peningkatan Efisiensi Ritel - Setiabudi, Edo; Cahyana, Atikha Sidhi (Indonesian Journal of Innovation Studies, 2024)
Minimarkets face challenges of overcrowding and prolonged wait times, often due to suboptimal cashier staffing. This study aims to determine the optimal number of cashiers to minimize queues. Using a single-phase multi-channel queuing model, data was collected through direct observation and quantitative analysis. Initial findings with two cashiers revealed varying wait times, prompting simulation experiments. Results indicated that adding a third cashier significantly reduced wait times to 0.41-2.45 minutes, enhancing service efficiency and customer satisfaction. Future research may explore longer observation periods and assess cost-effectiveness in staffing adjustments. Highlight: Data Analysis: Direct observation, quantitative data, and Excel processing for insights. Simulation Test: Arena software simulates cashier scenarios for service optimization. Efficiency Boost: Adding a cashier reduces wait times, enhancing customer satisfaction. Keywoard: Minimarket, Queuing Model, Cashier Optimization, Service Efficiency, Customer Satisfaction.